Dinaric fir-beech forests (Omphalodo-Fagetum (Tregubov 1957) MARINČEK et al. 1993) on Blegoš - Marinček, Lojze (Hladnikia (Ljubljana), 1998)
An intrazonally extended dinaric fir-beech forest in the Prealpine region of Slovenia as the Omphalodo-Fagetum (Tregubov 1957) Marinček et al. 1993 ranunculetosum platanifolii subass. nova is described in this work.
Keywords: botanika; Rhododendron-Park Bremen; fitogeografija; gozdne združbe; Blegoš; Slovenia; Slovenija